AVALIAÇÃO DA GENOTOXICIDADE E MUTAGENICIDADE DO BIODENTINE - Logar, Gustavo de Almeida (2014)
The Biodentine is a new material suitable for various clinical situations in dentistry. Despite being a promising material, there are few studies evaluating the characteristics of this material, especially its genotoxicity and mutagenicity. Objective: This study aims to evaluate the genotoxic and mutagenic potential of Biodentine "in vivo". Methods: We used 24 Wistar albino rats, males were divided into 3 groups: A - 8 rats where specimens of Biodentine measuring 2 mm in diameter x 10mm length on the dorsum were placed, B - 8 rats, which received cyclophosphamide in single subcutaneous dose (50mg/kg) on the first day of the experiment (positive control group), C - 8 rats where specimens measuring 2 mm in diameter x 10mm long without Biodentine on the dorsum were placed (negative control group). After 24 hours, all animals were euthanized and material from bone marrow of femurs was collected to perform the Comet assay and micronucleus test. Results: Biodentine showed levels of DNA damage (tail intensity %) in bone marrow cells of 23.57 ± 7.70, cyclophosphamide of 27,43 ± 7,40 and negative control of 24.75 ± 5 55 (p < 0.05). The average number of micronuclei in the exposed Biodentine group was 6.25 (standard deviation - SD = 3.53), in the group exposed to cyclophosphamide was 9.75 (SD = 2.49) and negative control group was 0.75 (SD = 1.03) (p < 0.0001). Conclusion: The Biodentine showed an increase in the frequency of micronuclei, but no genotoxicity effect by the Comet assay.